13x-7=2+910x

Simple and best practice solution for 13x-7=2+910x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13x-7=2+910x equation:


Simplifying
13x + -7 = 2 + 910x

Reorder the terms:
-7 + 13x = 2 + 910x

Solving
-7 + 13x = 2 + 910x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-910x' to each side of the equation.
-7 + 13x + -910x = 2 + 910x + -910x

Combine like terms: 13x + -910x = -897x
-7 + -897x = 2 + 910x + -910x

Combine like terms: 910x + -910x = 0
-7 + -897x = 2 + 0
-7 + -897x = 2

Add '7' to each side of the equation.
-7 + 7 + -897x = 2 + 7

Combine like terms: -7 + 7 = 0
0 + -897x = 2 + 7
-897x = 2 + 7

Combine like terms: 2 + 7 = 9
-897x = 9

Divide each side by '-897'.
x = -0.01003344482

Simplifying
x = -0.01003344482

See similar equations:

| 2(m+2)+4=m | | 2(0)+4=x | | 4(2x-3)+5=-71 | | 2(-3)+4=x | | 16s+10=4 | | -2(x+9)=-36 | | 4a+7(a-4)+6(a+8)=9 | | 2y+66=3y-24 | | 7y=44 | | x+4=2y | | 3(2)= | | 2-6-5-13-(-25)=p | | (2)(2)(2)= | | 8x-6x=-2 | | 28-(-8)-3=m | | x^2+x+0.5=0 | | 11d=11 | | X=-8+5x | | -12-25-32-(-9)=p | | -4-4=8-7x | | 15y=150 | | 14-.666666x=18 | | x+-24=10 | | 13.374x^2-258.431x+1724.415=0 | | -4x-5+x=4 | | -5(3q+9)=45 | | 15=.6n | | -4=4(6g-12)-2y | | 6-3x+2x=9x+26 | | .6x+22=28 | | -(4)(-2)= | | 3x-10=x+8 |

Equations solver categories